Identification of ocular regulatory functions of core histone variant H3.2. (January 2023) - Vetrivel, Sharmilee; Truong, Dong-Jiunn Jeffery; Wurst, Wolfgang; Graw, Jochen; Giesert, Florian
Abstract: The posttranscriptional modifications (PTM) of the Histone H3 family play an important role in ocular system differentiation. However, there has been no study on the nature of specific Histone H3 subtype carrying these modifications. Fortuitously, we had previously identified a dominant small-eye mutant Aey69 mouse with a mutation in the H3.2 encoding Hist2h3c1 gene (Vetrivel et al., 2019). In continuation, in the present study, the role of Histone H3.2 with relation to the microphtalmic Aey6 9 has been elaborated. Foremost, a transgenic mouse line expressing the fusion protein H3.2-GFP was generated using Crispr/Cas9. The approach was intended to confer a unique tag to the Hist2h3c1 gene which is similar in sequence and encoded protein structure to other histones. The GFP tag was then used for ChIP Seq analysis of the genes regulated by H3.2. The approach revealed ocular specific H3.2 targets including Ephrin family genes. Altered enrichment of H3.2 was found in the mutant Aey69 mouse, specifically around the ligand Efna5 and the receptor Ephb2 . The effect of this altered enrichment on Ephrin signaling was further analysed by QPCR and immunohistochemistry. This study identifies Hist2h3c1 encoded H3.2 as an important epigenetic player in ocular development. By binding to specific regions of ocular developmental factors Histone H3.2 facilitates the function of these genes for successful early ocular development. Highlights: Primary characterization and development of Histone H3.2-GFP mouse line. H3.2 has an irreplaceable role in eye development and microphthalmia. The epigenetic role of H3.2 in early ocular morphogenesis is through Ephrin signaling.